Numerical simulation of premixed H2–air cellular tubular flames. Issue 2 (3rd March 2016) - Hall, Carl Alan; Pitz, Robert Wendell
Abstract : The detailed flame structure of laminar premixed cellular flames in the tubular domain is simulated in 2D using a fully-implicit primitive variable finite difference formulation that includes multicomponent transport and detailed chemical kinetics. Numerical results for H2 /air flames are presented and compared against spatially resolved experimental measurements of temperature and chemical species including atomic H and OH. The experimental results compare well for flame structure and cell number, despite the numerical model under-predicting the peak temperature by 200 K. Numerical experiments were performed to assess the ability for cellular tubular flames to impact experimental and numerical investigations of practical flames. The cellular flame structure is found to provide a highly sensitive geometry that is useful for validating diffusive transport modelling approximations. This capability is exemplified through the development of a simple and accurate approximation for thermal diffusion (i.e. the Soret effect) that is suitable for practical combustion codes.